Cerebral hemorrhage as the initial manifestation in patients with systemic cancer. (2nd January 2018) - Huang, Gelun; Chen, Li; Qin, Chao; Cheng, Daobin; Lu, Qiuhong; Yu, Lixia; Liang, Zhijian
ABSTRACT: Background : Cerebral hemorrhage as well as ischemic stroke is one of the common complications among patients with cancer. Ischemic stroke could be the initial manifestation in some patients with cancer. Meanwhile, some patients with cancer also could present cerebral hemorrhage as the initial manifestation, and further studies are required to determine whether these patients have their unique clinical features. Aim: To investigate the clinical features and underlying pathogenesis of concealed systemic cancer patients with cerebral hemorrhage as the initial manifestation. Methods: The clinical data of patients with concealed systemic cancer who presented cerebral hemorrhage as the initial manifestation registered at the First Affiliated Hospital of Guangxi Medical University from January 2010 to December 2015 were prospectively collected and analyzed. Results: Seventeen systemic cancer patients with cerebral hemorrhage as the initial manifestation (0.02%) were ultimately enrolled from 8, 326 patients with cerebral hemorrhage. Three patients had traditional risk factors, but the other 14 patients did not. The common subtypes of malignancy were lung cancer, liver cancer, gastric carcinoma, rectal cancer and melanoma. Most patients (11/17, 64.7%) had elevated plasma levels of cancer biochemical markers, including cancer antigen (CA)125, CA153 and CA199, carcino-embryonic antigen, and alpha fetal protein. Coagulopathy was observed in 15 patients. Conclusion: The concealed systemic cancer patients with cerebral hemorrhage as the initial manifestation may lack conventional vascular risk factors but did present coagulopathy and elevated plasma levels of cancer biochemical markers. Coagulopathy might be responsible for the cerebral hemorrhage.